MENYERDERHANAKAN PELAKSANAAN PEMILU SERENTAK - Bismar Arianto (Bawaslu Provinsi Kepulauan Riau, 2019)
Indonesia, in 2019, held concurrent elections to determine the president, vice president and legislative members in one day.However, this major political event left some complexity in its implementation. This paper offered a solution for the implementation of the next concurrent elections, if any, namely through simplification by separating between national and regional elections and the use of effective and efficient technology.